(untitled) (LACCEI, 2024)
The present research had the objective of analyzing the relationship between the managerial skills of the leaders of the Mypes and the sales environment of the companies, focusing on the dimensions of customer service, relationship building and market. The sample n=425 where p-value ≤ 0.01 determined non-normality Cronbach’s Alpha is 0.753 and Spearman’s Rho is 0.259 for managerial skills. Kendal’s Thau test 0.25 explains moderate correlation in the Ordinal Logistic Correlation. Stochastic simulation with 14,000 tests indicates the 95% interval is between 4.10 and 4.29 confirming that they indicate that managerial skills are significantly related to the sales domain, both in the customer service dimension and in the relationship building dimension. In addition, dialogue and expression was found to be the most influential dimension of managerial skills in the sales domain. [9] [10] also suggest that the development of managerial skills, especially in dialogue and expression, can be an effective strategy to improve the sales environment of companies, contributing to their growth and sustainability.